[Crowd in University Union plaza listening to speaker on stage?] (1995)
A group of approximately twenty students are sitting on concrete stairs. A few of the students are reading or studying and others are speaking to the other students. Most other students are watching something not visible in the photograph, possibly a speaker on the University Union plaza stage.